The evaluation of the attractiveness of the tourist commune as conditioning of the development of agricultural tourism farms = Ocena atrakcyjności turystycznej gminy jako uwarunkowanie rozwoju gospodarstw agroturystycznych - Brelik, Agnieszka; Kułyk, Piotr (Zielona Góra: Faculty of Economics and Management Press)
The paper presents the relationship between the variables of the attractiveness of communities of the Wets Pomeranian and economic, social and ecological variables as feature of agritourism farms owners. The x 2 test of independence was used in order to identify factors differentiating the attractiveness of the surveyed communities by the farmhouses and the relationship between independence. The attention was drawn to the concept of multifunctionality of agriculture and the importance of the tourism activities.
Keywords: rolnictwo; agroturystyka; wielofunkcyjność rolnictwa; agriculture; agritourism; multifunctional agriculture